The Effectiveness Of Implementing The Project Based Learning Model In Enhancing The Comprehension Of Islamic Education For The Junior High School Students: Indonesia - Mirani Wardani, Aisha; Edi Cahyono (International Journal of Education, Vocational and Social Science, 2024)
The purpose of this study is to provide empirical evidence on the application of the Project-Based Learning (PjBL) model in differentiating the level of comprehension of Islamic Education(PAI) among students. This research employs a quantitative method. The results of the studyshows that 1) This indicates that there is no significant difference in student learning outcomesbetween SMP 1 and SMP 2 categories. The use of the PjBL model did not result in a differentlevel of understanding compared to those who are not using it. 2) There is a significantdifference in learning outcomes between male and female students. 3) There is no significantdifference in the average educational level of the parents. 4) There is no significant differencein the average occupation category of the parents.